Efeito do complexo de inclusão contendo α-terpineol e β-ciclodextrina na hiperalgesia não inflamatória em roedores - Oliveira, Makson Gleydson Brito de (2015)
α-Terpineol (TPN) is an alcoholic monoterpene present in the essential oil of oregano and thyme, having anticonvulsant, antinociceptive and anti-inflammatory properties. The TPN analgesic activity is associated with its actions in the central nervous system (CNS), what can suggest that TPN can act on dysfunctional chronic pain, such as fibromyalgia (FM). The FM is a chronic rheumatic disease with pathophysiology related to alterations in neurotransmission systems. The current therapy for FM is mainly characterized by pharmacotherapeutic conduct; however, there is significant drug resistance. Thus, the aim of this study was to evaluate the possible anti-hyperalgesic effect of an inclusion complex containing TPN and β-cyclodextrin (βCD) in the non-inflammatory chronic muscle pain model (considered to be a FM model) in rodents. The TPN-βCD complex was prepared and characterized by thermogravimetry (TG), absorption spectroscopy in the infrared Fourier transform (FTIR) and scanning electron microscopy (SEM). Albino Swiss mice were used, weighing between 20 and 30 g. The non-inflammatory chronic muscle pain model was induced by two injections of acid saline (pH 4.0 - 20 uL) into the left gastrocnemius, 5 days apart. After induction, the animals were treated with TPN-βCD (25, 50 or 100 mg/kg, p.o.), vehicle (0.9% saline, p.o.) or tramadol (5 mg/kg; i.p.) for 10 consecutive days. An hour after the treatment, it was measured the mechanical hyperalgesia through digital analgesimeter, the motor performance through the Rota-Rod and muscle strength through the Grip Strength Meter. In addition, it was tested the action of the administration of ondansetron and naloxone (opioid and serotonin antagonists, respectively) in the TPN analgesic action. The results were expressed as mean ± standard error and the differences between groups were analyzed using ANOVA followed by Tukey's test. After incorporation of TPN in βCD, the complexes were characterized physical chemically by different methods: TG, FTIR and SEM. These results together suggested the formation of TPN-βCD complex. The oral treatment with TPN-βCD, in all doses, produced a significant reduction (p <0.001) in the mechanical hyperalgesia without causing any changes in motor coordination. The muscle strength increased after the administration of the highest dose. The analgesic time effect in animals treated with TPN-βCD complex was over four hours to the free αTPN, being these difference statistically significant (p <0.01). The analgesic effect observed was reversed by systemic administration of naloxone or ondansetron. Corroborating these findings, the "docking" study confirmed the possible interaction of αTPN with opioid (mu, kappa, delta) and serotonin receptors. Thus, it can be concluded that the TPN-βCD complex reduced the mechanical hyperalgesia in the chronic muscle pain model, probably due to activation of CNS areas, possibly acting on opioid and serotonin receptors.